THEORETICAL CALCULATION OF CERTAIN PARAMETERS OF A COMBINED COULTER - A.N. Kalabushev; N.P. Laryushin; V.V. Shumaev (Volga Region Farmland, 2019)
It is known that the uniform distribution of seeds and fertilizers over the depth and length of the row is the most important indicator when sowing grain seeds. Existing drill coulters for sowing seeds of grain crops do not fully meet these requirements. A solution to one of the actual problems of sowing crops with simultaneous fertilization is considered – laying the seeds on a compacted bed while excluding their contact with the furrow walls and without dropping the furrows during the laying of seeds and fertilizers, which affects the uniform distribution of seeds along the row and fertilizers seeding depth and, as a result, crop yield. For this purpose, theoretical studies of the inclination angle of the seeding channel and the width of the seedbed firmer were carried out, and the density of the soil at the bottom of the furrow was calculated. When these conditions are met, the seeds and fertilizers do not bounce off the furrow walls and lie on the firmed seedbed evenly, as a result the crop yield is increased. The authors have developed and manufactured a new type of combined coulter, which eliminates all the described disadvantages [1, 2].